2024
DOI: 10.1007/s10902-024-00720-3
|View full text |Cite
|
Sign up to set email alerts
|

Feeling Important, Feeling Well. The Association Between Mattering and Well-being: A Meta-analysis Study

Monica Paradisi,
Camilla Matera,
Amanda Nerini

Abstract: Perception of mattering, the feeling of being important to others (Rosenberg & McCullogh in Community Ment Health J 2:163–182, 1981), is receiving increasing attention as a factor that promotes well-being. Individual well-being has been defined in different ways, such as hedonic, as in a deep satisfaction with life (Diener & Lucas in Well-being: Foundations of Hedonic Psychology 213, 1999), eudaimonic, as in the realization of the true self (Ryff in Curr Dir Psychol Sci 4(4):99–104, 1995), and holistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 89 publications
0
0
0
Order By: Relevance
“…Scarpa et al, (2021) found that general mattering was predictive of higher overall, interpersonal, community, occupational, physical well-being, psychological, and economic well-being. This means that mattering impacts many different domains of an individual's life and health, consistent with the positive relationship between mattering and holistic well-being (Paradisi et al, 2024). A study by Giangrasso et al, (2021) found university students with higher levels of general mattering were more likely to be satisfied with their life, than those with lower feelings of mattering.…”
Section: Mattering and Wellbeingmentioning
confidence: 66%
“…Scarpa et al, (2021) found that general mattering was predictive of higher overall, interpersonal, community, occupational, physical well-being, psychological, and economic well-being. This means that mattering impacts many different domains of an individual's life and health, consistent with the positive relationship between mattering and holistic well-being (Paradisi et al, 2024). A study by Giangrasso et al, (2021) found university students with higher levels of general mattering were more likely to be satisfied with their life, than those with lower feelings of mattering.…”
Section: Mattering and Wellbeingmentioning
confidence: 66%